Factors associated with satisfaction with community-based non-medicalized counseling and testing using HIV rapid tests among MSM in France. Issue 10 (2nd October 2016) - Préau, Marie; Lorente, Nicolas; Sagaon-Teyssier, Luis; Champenois, Karen; Gall, Jean Marie Le; Mabire, Xavier; Spire, Bruno; Mora, Marion; Yazdanpanah, Yazdan; Suzan, Marie; ,
ABSTRACT: The aims of the study were to determine the level of satisfaction of men who have sex with men (MSM) participating in two community-based non-medicalized counseling and testing programs (ANRS-DRAG and ANRS-COM'TEST) offering HIV rapid tests (hereafter CBOffer), and to identify factors associated with satisfaction. Between 2009 and 2011, 436 participants voluntarily benefited from a CBOffer in the two programs. They completed self-administered questionnaires before and after testing. Psychosocial scores were constructed using principal component analyses to reflect the following dimensions: post-test satisfaction, avoidance of at-risk situations as a HIV risk-reduction strategy, and attitudes towards condom use. Logarithmic regression of the post-test satisfaction score was performed on these scores and on other selected explanatory variables, including the variable "self-identification as homosexual or bisexual". Post-test satisfaction ranged between 90–99 and below 90 for 50% and 25% of the participants, respectively. Post-test satisfaction with the CBOffer was independently associated with self-defined sexuality, meeting place for sexual partners, participants' attitudes about being HIV-positive, and condom use. The very high level of satisfaction was associated with both personal and socio-behavioral factors. Vulnerable MSM could be targeted better and, accordingly, could use this offer more frequently as a combined prevention tool.